2017
DOI: 10.1017/s0022029916000807
|View full text |Cite
|
Sign up to set email alerts
|

An across-breed genome wide association analysis of susceptibility to paratuberculosis in dairy cattle

Abstract: Paratuberculosis is a chronic disease of ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). It occurs worldwide and causes a significant loss in the animal production industry. There is no cure for MAP infection and vaccination is problematic. Identification of genetics of susceptibility could be a useful adjunct for programs that focus on management, testing and culling of diseased animals. A case-control, genome-wide association study (GWAS) was conducted using Holstein and Jersey cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Color version available online. Candidate genes BTA1 Settles et al, 2009;Pant et al, 2010;Zanella et al, 2011;Minozzi et al, 2012;Alpay et al, 2014;Zare et al, 2014aSOD1, SSRG, SCL33A1, LDLRAD3, KCNAB1, GMPS, TUBA3D BTA2 Kirkpatrick et al, 2011Alpay et al, 2014;Sallam et al, 2017CREB1 BTA3 Settles et al, 2009Kirkpatrick et al, 2011;Zare et al, 2014b;Kiser et al, 2017FOXJ3, EDN2, CTPS, CITED4, NFYC, BCAR3 BTA4 Kirkpatrick et al, 2011van Hulzen et al, 2012DLD, Q28899, LAMB4, Q6Q146, PNPLA8, LOC784535, Q2YDK7, Q17QP5, EPDR1 BTA5 Settles et al, 2009Pant et al, 2010;Kirkpatrick et al, 2011;...…”
Section: Gwas and Functional Analysesmentioning
confidence: 99%
“…Color version available online. Candidate genes BTA1 Settles et al, 2009;Pant et al, 2010;Zanella et al, 2011;Minozzi et al, 2012;Alpay et al, 2014;Zare et al, 2014aSOD1, SSRG, SCL33A1, LDLRAD3, KCNAB1, GMPS, TUBA3D BTA2 Kirkpatrick et al, 2011Alpay et al, 2014;Sallam et al, 2017CREB1 BTA3 Settles et al, 2009Kirkpatrick et al, 2011;Zare et al, 2014b;Kiser et al, 2017FOXJ3, EDN2, CTPS, CITED4, NFYC, BCAR3 BTA4 Kirkpatrick et al, 2011van Hulzen et al, 2012DLD, Q28899, LAMB4, Q6Q146, PNPLA8, LOC784535, Q2YDK7, Q17QP5, EPDR1 BTA5 Settles et al, 2009Pant et al, 2010;Kirkpatrick et al, 2011;...…”
Section: Gwas and Functional Analysesmentioning
confidence: 99%
“…Other studies have also investigated the genetic architecture of MAP infection status in cattle. Significant genomic regions have been reported on various chromosomes such as BTA1 (Alpay et al, 2014), BTA2 (Alpay et al, 2014;Sallam et al, 2017), BTA3 (Settles et al, 2009;Zare et al, 2014;Sallam et al, 2017), BTA4 and BTA5 (van Hulzen et al, 2012), BTA6 (Alpay et al, 2014;Sallam et al, 2017), BTA7 (Alpay et al, 2014), BTA8 (Kiser et al, 2017;Sallam et al, 2017), BTA9 (Settles et al, 2009), BTA10, BTA12, and BTA14 (Kiser et al, 2017), BTA16 (Zare et al, 2014;Kiser et al, 2017), BTA17 (Alpay et al, 2014;Zare et al, 2014), BTA18 (van Hulzen et al, 2012), BTA20 (Gonda et al, 2007), BTA22 (Kiser et al, 2017), BTA23 (Zare et al, 2014), BTA25 and BTA27 (Sallam et al, 2017), BTA28 (van Hulzen et al, 2012), and BTA29 (Alpay et al, 2014;Sallam et al, 2017).…”
mentioning
confidence: 99%
“…In comparison with this study, 2 recently published GWAS identified different positional candidate genes and QTL associated with JD. By conducting a combined across-breed GWAS, Sallam et al (2017) identified QTL on BTA2, BTA3, BTA6, BTA8, BTA25, BTA27, and BTA29 and also reported 2 positional candidate genes, BTN1A1 and TDP2, associated with JD (cases were defined as cows that were positive by either fecal culture or serum ELISA tests). In an another GWAS using BovineSNP50 data, where JD cases were defined as MAP tissue quantitative PCR and culture positive, Kiser et al (2017) identified 7 QTL located on BTA22 in Jerseys and 6 QTL located on BTA8, BTA10, BTA12, BTA14, and BTA16 in the combined Pacific Northwest and Northeast Holstein population by meta-analysis.…”
mentioning
confidence: 99%
“…2, 3, 4, 5). The polygenic nature of viral neutralization antibody level, response to vaccination, and immune related traits is something that has been previously reported in numerous studies such as those focused on porcine [17, 25], chicken [26, 27], cattle [2831], and mice [32]. In the six windows that accounted for more than 1% of the genetic variance in this study, no candidate genes were identified as none of the genes in those regions were annotated with Gene Ontology terms associated with immune response functions.…”
Section: Discussionmentioning
confidence: 93%